Timed interfaces - De Alfaro, Luca; Henzinger, Thomas A; Stoelinga, Mariëlle (Proceedings of the 2nd International Conference on Embedded Software)
We present a theory of timed interfaces, which is capable of specifying both the timing of the inputs a component expects from the environment, and the timing of the outputs it can produce. Two timed interfaces are compatible if there is a way to use them together such that their timing expectations are met. Our theory provides algorithms for checking the compatibility between two interfaces and for deriving the composite interface; the theory can thus be viewed as a type system for real-time interaction. Technically, a timed interface is encoded as a timed game between two players, representing the inputs and outputs of the component. The algorithms for compatibility checking and interface composition are thus derived from algorithms for solving timed games.

Antagonistic pathways in neurons exposed to body fluid regulate social feeding in Caenorhabditis elegans - Coates, Juliet C.; de Bono, Mario (Nature)
Wild isolates of Caenorhabditis elegans can feed either alone or in groups1,2. This natural variation in behaviour is associated with a single residue difference in NPR-1, a predicted G-protein-coupled neuropeptide receptor related to Neuropeptide Y receptors2. Here we show that the NPR-1 isoform associated with solitary feeding acts in neurons exposed to the body fluid to inhibit social feeding. Furthermore, suppressing the activity of these neurons, called AQR, PQR and URX, using an activated K+ channel, inhibits social feeding. NPR-1 activity in AQR, PQR and URX neurons seems to suppress social feeding by antagonizing signalling through a cyclic GMP-gated ion channel encoded by tax-2 and tax-4. We show that mutations in tax-2 or tax-4 disrupt social feeding, and that tax-4 is required in several neurons for social feeding, including one or more of AQR, PQR and URX. The AQR, PQR and URX neurons are unusual in C. elegans because they are directly exposed to the pseudocoelomic body fluid3. Our data suggest a model in which these neurons integrate antagonistic signals to control the choice between social and solitary feeding behaviour.

Social feeding in Caenorhabditis elegans is induced by neurons that detect aversive stimuli - de Bono, Mario; Tobin, David M.; Davis, M. Wayne; Avery, Leon; Bargmann, Cornelia I. (Nature)
Natural Caenorhabditis elegans isolates exhibit either social or solitary feeding on bacteria. We show here that social feeding is induced by nociceptive neurons that detect adverse or stressful conditions. Ablation of the nociceptive neurons ASH and ADL transforms social animals into solitary feeders. Social feeding is probably due to the sensation of noxious chemicals by ASH and ADL neurons; it requires the genes ocr-2 and osm-9, which encode TRP-related transduction channels, and odr-4 and odr-8, which are required to localize sensory chemoreceptors to cilia. Other sensory neurons may suppress social feeding, as social feeding in ocr-2 and odr-4 mutants is restored by mutations in osm-3, a gene required for the development of 26 ciliated sensory neurons. Our data suggest a model for regulation of social feeding by opposing sensory inputs: aversive inputs to nociceptive neurons promote social feeding, whereas antagonistic inputs from neurons that express osm-3 inhibit aggregation.

Implementation of shape grammar for plan analysis - Mallick, Sanhita; Krishnendu Chatterjee; Merchant, Arif N; Dasgupta, Pallab

Patch-clamp recording in brain slices with improved slicer technology - Geiger, Jörg; Bischofberger, Joseph; Vida, Imre; Fröbe, Ulrich; Pfitzinger, S; Weber, H.; Haverkampf, Klaus; Jonas, Peter M (Pflugers Archiv : European Journal of Physiology)
The use of advanced patch-clamp recording techniques in brain slices, such as simultaneous recording from multiple neurons and recording from dendrites or presynaptic terminals, demands slices of the highest quality. In this context the mechanics of the tissue slicer are an important factor. Ideally, a tissue slicer should generate large-amplitude and high-frequency movements of the cutting blade in a horizontal axis, with minimal vibrations in the vertical axis. We developed a vibroslicer that fulfils these in part conflicting requirements. The oscillator is a permanent-magnet-coil-leaf-spring system. Using an auto-resonant mechano-electrical feedback circuit, large horizontal oscillations (up to 3 mm peak-to-peak) with high frequency (,90 Hz) are generated. To minimize vertical vibrations, an adjustment mechanism was employed that allowed alignment of the cutting edge of the blade with the major axis of the oscillation. A vibroprobe device was used to monitor vertical vibrations during adjustment. The system is based on the shading of the light path between a light-emitting diode (LED) and a photodiode. Vibroprobe monitoring revealed that the vibroslicer, after appropriate adjustment, generated vertical vibrations of <1 µm, significantly less than many commercial tissue slicers. Light- and electron-microscopic analysis of surface layers of slices cut with the vibroslicer showed that cellular elements, dendritic processes and presynaptic terminals are well preserved under these conditions, as required for patch-clamp recording from these structures.

Methods of generating three-dimensional digital models of objects by wrapping point cloud data points - Edelsbrunner, Herbert; Fu, Ping
A method of automatic conversion of a physical object into a three-dimensional digital model. The method acquires a set of measured data points on the surface of a physical model. From the measured data points, the method reconstructs a digital model of the physical object using a Delaunay complex of the points, a flow strcuture of the simplicies in the Delaunay complex and retracting the Delaunay complex into a digital model of the physical object using the flow structure. The method then outputs the digital model of the physical object.

Homeostatic maintenance of neuronal excitability by burst discharges in vivo - Buzsáki, György; Csicsvari, Jozsef L; Dragoi, George; Harris, Kenneth; Henze, D.; Hirase, Hajima (Cerebral Cortex)
Information in neuronal networks is thought to be represented by the rate of discharge and the temporal relationship between the discharging neurons. The discharge frequency of neurons is affected by their afferents and intrinsic properties, and shows great individual variability. The temporal coordination of neurons is greatly facilitated by network oscillations. In the hippocampus, population synchrony fluctuates during theta and gamma oscillations (10-100 ms scale) and can increase almost 10-fold during sharp wave bursts. Despite these large changes in excitability in the sub-second scale, longer-term (minute-scale) firing rates of individual neurons are relatively constant in an unchanging environment. As a result, mean hippocampal output remains stable over time. To understand the mechanisms responsible for this homeostasis, we address the following issues: (i) Can firing rates of single cells be modified? (ii) Once modified, what mechanism(s) can maintain the changes? We show that firing rates of hippocampal pyramidal cells can be altered in a novel environment and by Hebbian pairing of physiological input patterns with postsynaptic burst discharge. We also illustrate a competition between single spikes and the occurrence of spike bursts. Since spike-inducing (suprathreshold) inputs decrease the ability of strong ('teaching') inputs to induce a burst discharge, we propose that the single spike versus burst competition presents a homeostatic regulatory mechanism to maintain synaptic strength and, consequently, firing rate in pyramidal cells.

General models of multilocus evolution - Kirkpatrick, Mark; Johnson, Toby; Barton, Nicholas H (Genetics)
In 1991, Barton and Turelli developed recursions to describe the evolution of multilocus systems under arbitrary forms of selection. This article generalizes their approach to allow for arbitrary modes of inheritance, including diploidy, polyploidy, sex linkage, cytoplasmic inheritance, and genomic imprinting. The framework is also extended to allow for other deterministic evolutionary forces, including migration and mutation. Exact recursions that fully describe the state of the population are presented; these are implemented in a computer algebra package (available on the Web at http://helios.bto.ed.ac.uk/evolgen). Despite the generality of our framework, it can describe evolutionary dynamics exactly by just two equations. These recursions can be further simplified using a "quasi-linkage equilibrium" (QLE) approximation. We illustrate the methods by finding the effect of natural selection, sexual selection, mutation, and migration on the genetic composition of a population.

Combinatorial synthesis of genetic networks - Guet, Calin C; Elowitz, Michael; Hsing, Weihong; Leibler, Stanislas (Science)
A central problem in biology is determining how genes interact as parts of functional networks. Creation and analysis of synthetic networks, composed of well-characterized genetic elements, provide a framework for theoretical modeling. Here, with the use of a combinatorial method, a library of networks with varying connectivity was generated in Escherichia coli. These networks were composed of genes encoding the transcriptional regulators Lacl, TetR, and lambda Cl, as well as the corresponding promoters. They displayed phenotypic behaviors resembling binary logical circuits, with two chemical “inputs” and a fluorescent protein “output.” Within this simple system, diverse computational functions arose through changes in network connectivity. Combinatorial synthesis provides an alternative approach for studying biological networks, as well as an efficient method for producing diverse phenotypes in vivo.

Gating, modulation and subunit composition of voltage-gated K(+) channels in dendritic inhibitory interneurones of rat hippocampus - Lien, Cheng; Martina, Marco; Schultz, Jobst; Ehmke, Heimo; Jonas, Peter M (Journal of Physiology)
GABAergic interneurones are diverse in their morphological and functional properties. Perisomatic inhibitory cells show fast spiking during sustained current injection, whereas dendritic inhibitory cells fire action potentials with lower frequency. We examined functional and molecular properties of K(+) channels in interneurones with horizontal dendrites in stratum oriens-alveus (OA) of the hippocampal CA1 region, which mainly comprise somatostatin-positive dendritic inhibitory cells. Voltage-gated K(+) currents in nucleated patches isolated from OA interneurones consisted of three major components: a fast delayed rectifier K(+) current component that was highly sensitive to external 4-aminopyridine (4-AP) and tetraethylammonium (TEA) (half-maximal inhibitory concentrations < 0.1 mM for both blockers), a slow delayed rectifier K(+) current component that was sensitive to high concentrations of TEA, but insensitive to 4-AP, and a rapidly inactivating A-type K(+) current component that was blocked by high concentrations of 4-AP, but resistant to TEA. The relative contributions of these components to the macroscopic K(+) current were estimated as 57 +/- 5, 25 +/- 6, and 19 +/- 2 %, respectively. Dendrotoxin, a selective blocker of Kv1 channels had only minimal effects on K(+) currents in nucleated patches. Coapplication of the membrane-permeant cAMP analogue 8-(4-chlorophenylthio)-adenosine 3':5'-cyclic monophosphate (cpt-cAMP) and the phosphodiesterase blocker isobutyl-methylxanthine (IBMX) resulted in a selective inhibition of the fast delayed rectifier K(+) current component. This inhibition was absent in the presence of the protein kinase A (PKA) inhibitor H-89, implying the involvement of PKA-mediated phosphorylation. Single-cell reverse transcription-polymerase chain reaction (RT-PCR) analysis revealed a high abundance of Kv3.2 mRNA in OA interneurones, whereas the expression level of Kv3.1 mRNA was markedly lower. Similarly, RT-PCR analysis showed a high abundance of Kv4.3 mRNA, whereas Kv4.2 mRNA was undetectable. This suggests that the fast delayed rectifier K(+) current and the A-type K(+) current component are mediated predominantly by homomeric Kv3.2 and Kv4.3 channels. Selective modulation of Kv3.2 channels in OA interneurones by cAMP is likely to be an important factor regulating the activity of dendritic inhibitory cells in principal neurone-interneurone microcircuits.

Fast synaptic inhibition promotes synchronized gamma oscillations in hippocampal interneuron networks - Bartos, Marlene; Vida, Imre; Frotscher, Michael; Meyer, Axel; Monyer, Hannah; Geiger, Jörg; Jonas, Peter M (PNAS)
Networks of GABAergic interneurons are of critical importance for the generation of gamma frequency oscillations in the brain. To examine the underlying synaptic mechanisms, we made paired recordings from "basket cells" (BCs) in different subfields of hippocampal slices, using transgenic mice that express enhanced green fluorescent protein (EGFP) under the control of the parvalbumin promoter. Unitary inhibitory postsynaptic currents (IPSCs) showed large amplitude and fast time course with mean amplitude-weighted decay time constants of 2.5, 1.2, and 1.8 ms in the dentate gyrus, and the cornu ammonis area 3 (CA3) and 1 (CA1), respectively (33-34 degrees C). The decay of unitary IPSCs at BC-BC synapses was significantly faster than that at BC-principal cell synapses, indicating target cell-specific differences in IPSC kinetics. In addition, electrical coupling was found in a subset of BC-BC pairs. To examine whether an interneuron network with fast inhibitory synapses can act as a gamma frequency oscillator, we developed an interneuron network model based on experimentally determined properties. In comparison to previous interneuron network models, our model was able to generate oscillatory activity with higher coherence over a broad range of frequencies (20-110 Hz). In this model, high coherence and flexibility in frequency control emerge from the combination of synaptic properties, network structure, and electrical coupling.

Presynaptic short-term depression is maintained during regulation of transmitter release at a GABAergic synapse in rat hippocampus - Hefft, Stefan; Kraushaar, Udo; Geiger, Jörg; Jonas, Peter M (Journal of Physiology)
To examine possible interactions between fast depression and modulation of inhibitory synaptic transmission in the hippocampus, we recorded from pairs of synaptically connected basket cells (BCs) and granule cells (GCs) in the dentate gyrus of rat brain slices at 34 degrees C. Multiple-pulse depression (MPD) was examined in trains of 5 or 10 inhibitory postsynaptic currents (IPSCs) evoked at frequencies of 10-100 Hz under several conditions that inhibit transmitter release: block of voltage-dependent Ca2+ channels by Cd2+ (10 microM), activation of gamma-amino-butyric acid type B receptors (GABA(B)Rs) by baclofen (10 microM) and activation of muscarinic acetylcholine receptors (mAchRs) by carbachol (2 microM). All manipulations led to a substantial inhibition of synaptic transmission, reducing the amplitude of the first IPSC in the train (IPSC1) by 72%, 61% and 29%, respectively. However, MPD was largely preserved under these conditions (0.34 in control versus 0.31, 0.50 and 0.47 in the respective conditions at 50 Hz). Similarly, a theta burst stimulation (TBS) protocol reduced IPSC1 by 54%, but left MPD unchanged (0.40 in control and 0.39 during TBS). Analysis of both fractions of transmission failures and coefficients of variation (CV) of IPSC peak amplitudes suggested that MPD had a presynaptic expression site, independent of release probability. In conclusion, different types of presynaptic modulation of inhibitory synaptic transmission converge on a reduction of synaptic strength, while short-term dynamics are largely unchanged.

Timing and efficacy of Ca(2+) channel activation in hippocampal mossy fiber boutons - Bischofberger, Josef; Geiger, Jörg; Jonas, Peter M (Journal of Neuroscience)
The presynaptic Ca2+ signal is a key determinant of transmitter release at chemical synapses. In cortical synaptic terminals, however, little is known about the kinetic properties of the presynaptic Ca2+ channels. To investigate the timing and magnitude of the presynaptic Ca2+ inflow, we performed whole-cell patch-clamp recordings from mossy fiber boutons (MFBs) in rat hippocampus. MFBs showed large high-voltage-activated Ca(2+) currents, with a maximal amplitude of approximately 100 pA at a membrane potential of 0 mV. Both activation and deactivation were fast, with time constants in the submillisecond range at a temperature of approximately 23 degrees C. An MFB action potential (AP) applied as a voltage-clamp command evoked a transient Ca2+ current with an average amplitude of approximately 170 pA and a half-duration of 580 microsec. A prepulse to +40 mV had only minimal effects on the AP-evoked Ca2+ current, indicating that presynaptic APs open the voltage-gated Ca2+ channels very effectively. On the basis of the experimental data, we developed a kinetic model with four closed states and one open state, linked by voltage-dependent rate constants. Simulations of the Ca2+ current could reproduce the experimental data, including the large amplitude and rapid time course of the current evoked by MFB APs. Furthermore, the simulations indicate that the shape of the presynaptic AP and the gating kinetics of the Ca2+ channels are tuned to produce a maximal Ca2+ influx during a minimal period of time. The precise timing and high efficacy of Ca2+ channel activation at this cortical glutamatergic synapse may be important for synchronous transmitter release and temporal information processing.

TwoB or not twoB: differential transmission at glutamatergic mossy fiber-interneuron synapses in the hippocampus - Bischofberger, Josef; Jonas, Peter M (Trends in Neurosciences)
Mossy fiber (MF) synapses are key stations for flow of information through the hippocampal formation. A major component of the output of the MF system is directed towards inhibitory interneurons. Recent studies have revealed that the functional properties of MF-interneuron synapses differ substantially from those of MF-CA3 pyramidal neuron synapses. Mossy-fiber-interneuron synapses in the stratum lucidum represent a continuum of functional subtypes, in which the subunit composition of postsynaptic AMPA receptors and NMDA receptors appears to be regulated in a coordinated manner.

Adaptive production of fighter males: queens of the ant Cardiocondyla adjust the sex ratio under local mate competition - Cremer, Sylvia; Heinze, Jürgen (Proceedings of the Royal Society of London Series B Biological Sciences)
Hamilton's concept of local mate competition (LMC) is the standard model to explain female-biased sex ratios in solitary Hymenoptera. In social Hymenoptera, however, LMC has remained controversial, mainly because manipulation of sex allocation by workers in response to relatedness asymmetries is an additional powerful mechanism of female bias. Furthermore, the predominant mating systems in the social insects are thought to make LMC unlikely. Nevertheless, several species exist in which dispersal of males is limited and mating occurs in the nest. Some of these species, such as the ant Cardiocondyla obscurior, have evolved dimorphic males, with one morph being specialized for dispersal and the other for fighting with nest-mate males over access to females. Such life history, combining sociality and alternative reproductive tactics in males, provides a unique opportunity to test the power of LMC as a selective force leading to female-biased sex ratios in social Hymenoptera. We show that, in concordance with LMC predictions, an experimental increase in queen number leads to a shift in sex allocation in favour of non-dispersing males, but does not influence the proportion of disperser males. Furthermore, we can assign this change in sex allocation at the colony level to the queens and rule out worker manipulation.

A method for analysing small-size specimens in GC-MS - Turillazzi, Stefano; Sledge, Matthew; Cremer, Sylvia; Heinze, Jürgen (Insect Social Life)
A particular Solid Injector needle, suitable for GC-MS analyses of small specimens, is described together with its application in a study on ants.

A transitional stage between the ergatoid and winged male morph in the ant Cardiocondyla obscurior - Cremer, Sylvia; Lautenschläger, Birgit; Heinze, Jürgen (Insectes Sociaux)
Males of the ant Cardiocondyla show a dispersal dimorphism of a winged and wingless morph. The loss of flight has lead to morphological reductions in the wingless (ergatoid) males and also affected body size, eye size and pigmentation. As ergatoid males mate exclusively inside the maternal nest, they underlie increased male-male competition and therefore have also evolved additional changes in behaviour and physiology: in contrast to winged males, ergatoid males are highly aggressive towards each other and their spermatogenesis is prolonged compared to all other hymenopteran males. In addition to these two male morphs, we found males with an intermediate appearance. These "intermorphic" males provide a transitional stage between normal males in most investigated morphological and physiological parameters. As they are produced extremely rarely and only in colonies that switch between pure ergatoid to mixed male production, we argue that they likely represent a developmental mistake. Parallels between the determination of male morphs and female castes (queen-worker dimorphism and worker polymorphism) might help to understand how the large potential of phenotypic plasticity in both sexes of social insects is realised during development.

Chemical mimicry: Male ants disguised by the queen's bouquet - Cremer, Sylvia; Sledge, Matthew; Heinze, Jürgen (Nature)
Males of the tropical ant Cardiocondyla obscurior are either wingless and aggressive or winged and docile, and both compete for access to virgin queens in the nest1, 2. Although the fighter males (ergatoids) attack and kill other ergatoids, they tolerate and even attempt to mate with their winged rivals. Here we show that the winged males avoid the aggression of wingless males by mimicking the chemical bouquet of virgin queens, but that their mating success is not reduced as a result. This example of female mimicry by vigorous males is surprising, as in other species it is typically used as a protective strategy by weaker males, and may explain the coexistence and equal mating success of two male morphs.

Algorithmic issues in modeling motion - Agarwal, Pankaj; Guibas, Leonidas; Edelsbrunner, Herbert; Erickson, Jeff; Isard, Michael; Har Peled, Sariel; Hershberger, John; Jensen, Christian; Kavraki, Lydia; Koehl, Patrice; Lin, Ming; Manocha, Dinesh; et al. (ACM Computing Surveys)
This article is a survey of research areas in which motion plays a pivotal role. The aim of the article is to review current approaches to modeling motion together with related data structures and algorithms, and to summarize the challenges that lie ahead in producing a more unified theory of motion representation that would be useful across several disciplines.

Topological persistence and simplification - Edelsbrunner, Herbert; Letscher, David; Zomorodian, Afra (Discrete & Computational Geometry)
We formalize a notion of topological simplification within the framework of a filtration, which is the history of a growing complex. We classify a topological change that happens during growth as either a feature or noise depending on its lifetime or persistence within the filtration. We give fast algorithms for computing persistence and experimental evidence for their speed and utility.